ASPEK PSIKOLOGI DAN KESEHATAN MENTAL DALAM PENDIDIKAN AQIDAH DAN IBADAH PESERTA DIDIK - Ahmad Syarifin (Universitas Islam Negeri Fatmawati Sukarno, 2018)
The issue of aqeedah and psychological aspects, as well as mental health in it are human needs. On the other hand, the highest needs of human beings are religion, religion is identical with belief, this belief is understood as a faith which in Islam manifests in the six pillars of faith. Psychologically humans need religion and one of the characteristics that humans are healthy is by the existence of religion. One of the mental health can be achieved through the Islamic method, through the correct implementation of the pillars of faith in daily life, so that the faith is not only imprinted in the heart, but is spoken with verbally and concretely in its behavior. The psychological aspects of worship can be seen from the nature of worship education itself. The essence is like the birth in man (psychologically) of the intensity of consciousness in thinking, then a Muslim wherever he is will feel bound to such ties of consciousness, therefore hu- mans will act systematically based on honesty and self-confidence. In addition, Muslims who feel bound by Allah will feel the delicacy and attitude of prioritizing God as a source, with worship like this that humans will have identity (self- development), because unity has strengthened itself